Pengaruh Perencanaan Pajak Terhadap Manajemen Laba yang di Moderasi Oleh Aset Pajak Tangguhan - Amara Destriana Gita Putri; Maharani (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research aims to analyze the effect of tax planning on earnings management which is moderated by deferred tax assets. Tax planning is measured using the Tax Retention Rate, Profit Management is measured by discretionary accruals, Deferred Tax Assets are measured by deferred tax assets. The population in this research is industrial sector companies listed on the Indonesia Stock Exchange in 2018-2022. The type of research used is associative quantitative. The data analysis technique used in this research is panel data regression analysis and processed using the Eviews 10 application. The variables used in this research are Tax Planning as the independent variable, Profit Management as the dependent variable and Deferred Tax Assets as a moderating variable. The research results based on the T test results are that Tax Planning has an influence on earnings management and Deferred Tax Assets cannot moderate the influence of tax planning on earnings management..